A northern planner's perspective: One opinion - Robertson, Ian D. (Canadian Institute of Planners, 1999)
Determining whether land-use planning in Canada's north has been successful is a question of perspective, attitude and political expectation. Most planning activity over the past thirty years has been reactionary rather than anticipatory - the result of external pressures over which people living here have little control. A "top-down" regional planning process directed by the Department of Indian Affairs and Northern Development failed because of inequalities in power, a lack of measurable objectives, and the absence of a shared vision. The settlement of land claims and the division of the Northwest Territories has created new opportunities for a community-driven, ecosystem-based approach to land and resource management. However, because no one asked the fundamental question of how much government is actually needed by 60,000 people, these changes have also increased the amount of bureaucracy. Most planners come north by choice, bringing along their southern background, training and perspective. The government towns of Goose Bay, Yellowknife and Whitehorse generally exhibit the developed form, attitudes to planning, and policy development found down south. In terms of physical layout and built form, traditional solutions area replicated from coast to coast. Planners have generally avoided the more complex social and economic problems. Planners need interdisciplinary, cross-cultural and community-development skills. They must understand how the contextual issues of scale, regional geography, and time affect their work, and be prepared to make the personal commitment required to become part of the communities in which they work. Prétendre que l'aménagement du territoire dans le Nord canadien est un succès ou un échec est une question de point de vue et de choix politique. La démarche des urbanistes au cours des trente dernières années était plus souvent faite d'opportunisme que d'anticipation; c'est-à-dire qu'elle a été et plus souvent l'objet de pressions extérieures hors de contrôle des populations locales. ...